Fracture toughness of fibre-reinforced plastics:: Effect of fibre type and temperature - Ünal, A (MINERALS, METALS & MATERIALS SOC, 1996)
Fracture toughness of composite materials disciplines are presented and described at their various levels of sophistication and attendant scales of application. In this paper, an investigation on the influence of various kinds of fibre and elevated temperature on fracture toughness is presented for the materials of polyester and epoxy resins as thermosetting plastics and E-Glass as a fibre composite material. Chopped Strand Mat (CSM), Plain Woven Glass Fabrics (PWGF) and Unidirectional Laminate (UL) were used as fibre material. For CSM and both PWGF and UL materials, the fibre volume ratio was selected 20%, 25%, 30% and 30%, 40%, 50% respectively. The Glass Reinforced Plastics (GRP) materials having above fibre volumes and 4, 6, 8, and 10 mm thickness, were manufactured by the Cold Molding Technique in the metallic molds. The compact Test Specimens (CT) prepared according to ASTM E-399, were used in the experiments. To comply with this standard, the geometrical ratio of a/W=0.5 selected and CT specimens were machined to satisfy the condition of W=4B which stands for 1 less than or equal to W/B less than or equal to 4. The fatigue precracking was created such that R=0. Fracture toughness was performed at 25, 50, 75, 100, and 125 degrees C by using Schenk-Trebel servo hydraulic tensile machine. The fractured surface photographs were taken by SEM and crack growth was inspected by optical microscope. At the end, fracture toughness of all specimens was calculated and plotted versus temperature and fibre volume ratio.
Keywords: MATRIX COMPOSITES; FIBER LENGTH; FATIGUE; Materials Science; Metallurgy & Metallurgical Engineering